Scrobicularia plana (Mollusca, Bivalvia) as a biomonitor for mercury contamination in Portuguese estuaries - Coelho, J. P.
The main goal of this research was to test the effectiveness of Scrobicularia plana to reflect environmental mercury concentrations, with the aim to propose it as a suitable, sentinel mercury biomonitor. Significant differences in mercury concentrations were observed between small and larger sized individuals in the most contaminated sampling sites, suggesting progressive mercury accumulation with size. Larger size classes did not significantly differ, however, indicating that organisms attain an equilibrium state between the mercury assimilation and excretion rates. Therefore, the average concentration of individuals larger than 2 cm shell length is indicative of the local contaminant bioavailability. The diet emerges as the source of contaminant incorporation in this species, which reflects sediment and suspended particulate matter (SPM) contamination regardless of the degree of environmental contamination. Such consistent bioaccumulation behavior, its widespread distribution, abundance, ease of collection, taxonomic identification and resistance to contamination, emphasize the usefulness of S. plana as a cosmopolitan biomonitor of mercury contamination in temperate estuarine systems.